Neurobiological insights into the effects of ultra-processed food on lipid metabolism and associated mental health conditions: a scoping review - Poon, Emily; Li, Christine; Schweitzer, Daniel; Akefe, Isaac (Frontiers in Nutrition, 2026)
BackgroundUltra-processed foods (UPFs) account for approximately 38% of the adult diet, corresponding with a global increase in the prevalence of mental illnesses. Understanding the relationship between UPF consumption and mental health is crucial for public health and clinical practice.ObjectivesTo uncover the association between consumption of ultra-processed food (UPF), dysregulated lipid metabolism, and increased risk of mental illnesses, including depression, anxiety, attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), eating disorders (ED), and food addiction (FA). In addition, this review explores the potential biological and behavioral mechanisms that may underlie these associations for each disorder.MethodsFollowing the PRISMA extension for scoping reviews guideline, a comprehensive search was conducted across PubMed, Web of Science, and EMBASE databases. The retrieved records, screened using Covidence, included English-language studies published between 2020 and 2025 that involved participants without significant comorbidities. Relevant data on associations and proposed mechanisms were extracted and synthesized using a narrative approach.ResultsUPF consumption was associated with dysregulated lipid metabolism and increased risk of Anxiety, Depression, ADHD, Autism, ED, and FA. Dose-dependent increases in risk were identified in all mental illnesses except for autism. Proposed mechanisms for all these increased risks included systemic low-grade inflammation, alterations in neuronal signaling, particularly dopamine and serotonin signaling pathways, and the influence of UPF additives on neurochemical regulation.ConclusionThere is a strong association between UPF consumption, disrupted lipid metabolism and increased risk of mental disorder in populations without significant comorbidities. Diets rich in minimally processed foods appear protective. The findings support the potential of public health initiatives aimed at reducing UPF consumption to mitigate the mental health burden. Future studies should focus on mechanistic pathways, UPF and minimally processed food consumption patterns to provide evidence for targeted dietary and policy interventions that improve health outcomes.